Media Informasi di Ranah Media Sosial: Perubahan Karakteristik dan Peran Jurnalistik Sebagai Media Baru - Almira Suci Maharani (Universitas Medan Area, 2022)
This article aims to see the changing characteristics and role of journalism as a new media. The rapid development of technology encourages all parties to move forward, including the mass media. Over time, various conventional mass media companies such as print media began to turn to online media as a means of reporting. Apart from news portals with big names, there are currently many independent news portals or individuals who choose to share information through social media accounts. The problem is focused on how journalists pay attention to the code of ethics in reporting information in the realm of social media. The data were collected through the document study method or literature review and non-participant observation. With literature review, the author takes references and examples from books that are relevant to the research title. The data that has been obtained were analyzed qualitatively. This study concludes that in online media, the writing style is more rigid and similar to conventional media such as newspapers. Meanwhile, in new media, the writing style looks more flexible and the journalist's perspective or personal view on the issues being reported is often more visible.